Navigating social media in education: challenges, recommendations, and a path forward / Dr. Farah Adilla Ab Rahman and Jeniwaty Mohd Jody - Ab Rahman, Farah Adilla; Mohd Jody, Jeniwaty (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The intersection of education and technology has become unavoidable and consequential in the contemporary digitally interconnected society. Consequently, the current educational terrain is undergoing a transformation towards the utilization of digital technologies for both teaching and learning (Rautela, 2022). Concurrently, social media (SM) is widely utilized for sharing content, initiating discussions, promoting businesses, and outpacing traditional media. Technological advancements play a crucial role in strengthening social media by mitigating security threats and improving overall reliability (Stergiou et al., 2018). As of January 2022, the global Internet user count has exceeded 4.95 billion, with approximately 4.62 billion individuals actively engaging on social media platforms (Johnson, 2022).